Strategic Responses of Incumbents to New Entry: The Effect of Ownership Structure, Capital structure, and focus - Khanna, Naveen; Tice, Sheri (Review of Financial Studies, 2000)
We examine how certain firm- and market-specific characteristics affect incumbent firms' responses to new entry into their local markets. Data comes from the discount department store industry where Wal-Mart entered a large number of markets in a short period of time. Consistent with existing research, larger and more profitable incumbents respond more aggressively to Wal-Mart's entry, while more highly levered incumbents respond less aggressively. Also, there is evidence that incumbent managers fight harder (possibly overinvest) when their job is at greater risk and high managerial ownership appears to reduce this agency problem. Incumbent firms behave differently in markets under attack by Wal-Mart than in markets not yet threatened, suggesting that some of the documented responses are specific to Wal-Mart's entry.